Figure 6 from: Sikes D, Stockbridge J (2013) Description of Caurinus tlagu, new species, from Prince of Wales Island, Alaska (Mecoptera, Boreidae, Caurininae). ZooKeys 316: 35-53. https://doi.org/10.3897/zookeys.316.5400 - Sikes, Derek; Stockbridge, Jill (Zenodo, 2013)
Figure 6 - Female Caurinus tlagu (UAM:Ento:159119) that had been cleared in KOH. A lateral view (broken abdomen), scale bar = 2 mm B face, scale bar = 0.5 mm C dorsal view, scale bar = 2 mm D ventral view, scale bar = 0.5 mm.